KELAYAKAN BOOKLET SUBMATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN PADA TANAMAN MONOKOTIL - Ersa Oktaviani; Entin Daningsih; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2021)
This study aimed to determine the feasibility of booklet of plant structure and function tissue submateria lwith additional information about the stomatal distribution and area as teaching material. The research method used was descriptive. Validation by 5 validators consisting of 2 lecturers of the Faculty of Teacher Training and Education (FKIP) Tanjungpura University and 3 biology teachers of class XI SMA using the 2013 curriculum and school accreditation at least B. The assessment uses 5 aspects and 12 criteria. The results of the validation analysis of teaching materials obtained an average CVR and CVI value of 0.95. The booklet needs improvement on content graphing. Therefore, the booklet teaching submaterial with additional information based on the stomatal distribution and area in monocots plant was suitable to be used in the learning process of the structure and function of plant in class in XI SMA.